2010
DOI: 10.1016/j.jsb.2010.06.019
|View full text |Cite
|
Sign up to set email alerts
|

An adaptive non-local means filter for denoising live-cell images and improving particle detection

Abstract: Fluorescence imaging of dynamical processes in live cells often results in a low signal-to-noise ratio. We present a novel feature-preserving non-local means approach to denoise such images to improve feature recovery and particle detection. The commonly used non-local means filter is not optimal for noisy biological images containing small features of interest because image noise prevents accurate determination of the correct coefficients for averaging, leading to over-smoothing and other artifacts. Our adapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 30 publications
0
44
0
Order By: Relevance
“…The average donor channel image was created from images with the 532 nm excitation, and the average acceptor image was created from images with the 635 nm excitation. Both images were filtered to enhance fluorescent spots and converted to images of fluorescent spot probabilities (25). Spots with probability above a set value were fit with a two…”
Section: Discussionmentioning
confidence: 99%
“…The average donor channel image was created from images with the 532 nm excitation, and the average acceptor image was created from images with the 635 nm excitation. Both images were filtered to enhance fluorescent spots and converted to images of fluorescent spot probabilities (25). Spots with probability above a set value were fit with a two…”
Section: Discussionmentioning
confidence: 99%
“…The denoising method becomes adaptive, i.e., the adaptive NLM (ANLM), when an NLM method adapts its h parameter values based on the characteristics of the image. 22,26,29,36,37 Previous studies have suggested that the optimal values for h could be selected to be proportional to the noise variation. 22,25 For an image with an unknown true noise variation, the noise level, σðx i Þ, at voxel x i , could be estimated by computing the minimal Euclidean distance of the weighted average of all blocks neighboring the voxel x i E Q -T A R G E T ; t e m p : i n t r a l i n k -; e 0 0 4 ; 3 2 6 ; 6 0 9…”
Section: Basics Of Nonlocal Means-based Denoisingmentioning
confidence: 99%
“…Patch-based filter (PBF) [4,11] is a state-of-the-art development of NLM filter in which the sizes of the searching windows are adaptively selected. However, for low SNR images containing particle-like features, such as fluorescence live-cell images with mixed Poisson-Gaussian noise contaminations [1][2][3][4], the Euclidean distance measured in greyscale images may not be robust for preserving the features [12]. Consequently, NLM filter and other algorithms that are based on this measurement can lead to loss of information and artefacts in denoised images.…”
Section: Introductionmentioning
confidence: 99%